Exploratory study among public servants in Kuching on the effectiveness of ACA'S Aerogram complain form as a communication tool to combating corruption. (Case study: Anti-Corruption Agency Kuching Branch) / Marcel Bulan Ngabong - Ngabong, Marcel Bulan (2005)
Corruption is interpreted as gratification. Therefore gratification here means money, donations, loan, fee, reward, valuable security, property, any office, dignity, employment, contract of employment or services, payment, any valuable consideration of any kind, any discount, commission, rebate, bonus, and any forbearance to demand any money, any other service or favor of any description, any offer, any undertakings or promise. As such, the government has set up an agency known as The Anti Corruption Agency of Malaysia (ACA) to act as an entrusted body to fight corruption. ACA’s journey in its fight to eradicate corruption is not shielded from obstacles a nd challenges that must be overcome with efficiency and effectiveness. As the work of ACA resembles a fight of enjoining what is right and forbidding what is wrong, ACA will be facing various obstacles. Nothing is easy in any fight and work implementation. The Agency will always face hurdles and trials. With unfaded spirit and carrying out work in the best way, excellence combined with an honest and sincere attitude, and by overcoming all obstacles with sincere efforts, ACA will achieve their target as set in their vision and mission.